Magnetic reconnection driven by electron dynamics. Issue 1 (December 2018) - Kuramitsu, Y.; Moritaka, T.; Sakawa, Y.; Morita, T.; Sano, T.; Koenig, M.; Gregory, C.; Woolsey, N.; Tomita, K.; Takabe, H.; Liu, Y.; Chen, S.; et al.
Abstract Magnetic reconnections play essential roles in space, astrophysical, and laboratory plasmas, where the anti-parallel magnetic field components re-connect and the magnetic energy is converted to the plasma energy as Alfvénic out flows. Although the electron dynamics is considered to be essential, it is highly challenging to observe electron scale reconnections. Here we show the experimental results on an electron scale reconnection driven by the electron dynamics in laser-produced plasmas. We apply a weak-external magnetic field in the direction perpendicular to the plasma propagation, where the magnetic field is directly coupled with only the electrons but not for the ions. Since the kinetic pressure of plasma is much larger than the magnetic pressure, the magnetic field is distorted and locally anti-parallel. We observe plasma collimations, cusp and plasmoid like features with optical diagnostics. The plasmoid propagates at the electron Alfvén velocity, indicating a reconnection driven by the electron dynamics. Magnetic reconnection is the process of releasing energy by magnetized and space plasma. Here the authors report experimental observation of magnetic reconnection in laser-produced plasma and the role of electron scaling on reconnection.